Challenges on Teaching and Learning English for Specific Purposes (ESP) for Indonesian Undergraduate Students - Yuni Awalaturrohmah Solihah; Viar Dwi Kartika; Fiki Setiawan (LET: Linguistics, Literature and English Teaching Journal, 2023)
This study examined the challenges both teachers and students in implementation of teaching and learning ESP. It focuses on mastering English in students’ needs relating to the specific fields. This used a qualitative study obtaining data from questionnaires and interviews. The findings showed that the students’ vocabulary mastery was an obstacle during learning ESP. It made the students felt difficult to comprehend the materials. Moreover, the teachers are supposed to prepare the ESP materials from textbooks and articles relating to the specific fields although there were lack of sources. However, learning ESP applied the students-centered activities and built an interaction between teachers and students during discussing and practicing the ESP materials. It encouraged the students to be active for their speaking skill improvement. It also assisted the students to enhance new vocabularies relating to the specific fields. Therefore, to achieve students’ comprehension in ESP, the teachers should develop ESP materials and method of teaching in order to deliver optimally the ESP contents.